One‐Year Outcome of Intensive Insulin Therapy Combined to Glucose‐Insulin‐Potassium in Acute Coronary Syndrome: A Randomized Controlled Study. Issue 11 (14th November 2017) - Bouida, Wahid; Beltaief, Kaouthar; Msolli, Mohamed Amine; Bzeouich, Nasri; Sekma, Adel; Echeikh, Malek; Mzali, Malek; Boubaker, Hamdi; Grissa, Mohamed Habib; Boukef, Riadh; Hassine, Mohsen; Dridi, Zohra; et al.
Abstract : Background: A number of factors may offset the cardioprotective effects of glucose‐insulin‐potassium (GIK) on outcome of patients with acute coronary syndrome, such as hyperglycemia induced by this cocktail infusion. We performed a study to evaluate the effect of intensive insulin therapy in association with GIK on 1‐year outcome in patients hospitalized for acute coronary syndrome. Methods and Results: In a randomized prospective controlled trial we included 772 patients with non–ST‐segment elevation acute coronary syndrome. Patients were randomized into 3 groups: GIKI2 group, who received GIK with intensive insulin therapy for 24 hours; GIK group, who received GIK with nonintensive insulin therapy; and control group, who received usual care. The primary outcome criteria were the rates of major cardiovascular events combining death, reinfarction, and stroke rate at 1 year. In addition, we measured platelet function assay‐100 and plasminogen activator inhibitor‐1 at admission and 24 hours later. Based on an intention‐to‐treat analysis, major cardiovascular events at 1 year was 12.8% in the GIKI2 group, 15.5% in the GIK group, and 20.5% in the placebo group; the difference was significant between the GIK2 and control groups ( P =0.01). Platelet function assay‐100 at 24 hours decreased significantly from baseline in the control group but not in the GIKI2 group. Plasminogen activator inhibitor‐1 decreased significantly in the GIKI2 group but significantly increased in the control group. Minor hypoglycemic events were more frequent in the GIKI2 group compared with other groups. Conclusions: GIKI2 led to improvement of 1‐year outcome rates in patients with non–ST‐segment elevation acute coronary syndrome. This beneficial effect was associated with a decrease in platelet reactivity and an increase on fibrinolysis tests. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00965406.